2023
DOI: 10.1111/anae.16202
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the success rate of tracheal intubation between stylet and bougie with a hyperangulated videolaryngoscope: a randomised controlled trial

D. Eum,
Y. J. Ji,
H. J. Kim

Abstract: SummaryHyperangulated videolaryngoscopes are known to increase the success rate of tracheal intubation in the setting of difficult airway management when used with a stylet or bougie. However, there is controversy over which adjunct is more useful. This randomised study aimed to compare first attempt tracheal intubation success rate between a stylet and bougie when using a hyperangulated videolaryngoscope. We recruited patients aged > 20 years who were scheduled for elective surgery under general anaesthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…I enjoyed the article by Eum et al [1], but as a very regular user of hyperangulated videolaryngoscopy, I am surprised by the results.…”
Section: Stylets Bougies and Hyperangulated Videolaryngoscopymentioning
confidence: 98%
See 1 more Smart Citation
“…I enjoyed the article by Eum et al [1], but as a very regular user of hyperangulated videolaryngoscopy, I am surprised by the results.…”
Section: Stylets Bougies and Hyperangulated Videolaryngoscopymentioning
confidence: 98%
“…We would like to thank Cook [1] for his interest in our research [2] and the opportunity to further discuss the use of hyperangulated videolaryngoscopes and their adjuncts.…”
Section: Stylets Bougies and Hyperangulated Videolaryngoscopy: A Replymentioning
confidence: 99%
“…We thank Drs Cafferkey and Ward [1] for their interest in our article [2]. To address the comment on the stylet's shape, we acknowledge its significance, as it substantially impacts the success of tracheal intubation.…”
Section: Intubation Aids In Hyperangulated Videolaryngoscopy: Essenti...mentioning
confidence: 99%
“…In this study, oral morphine was prescribed as required and intravenous morphine was supplemented for severe pain. Although 1 mg of intravenous morphine is equivalent to 3 mg by the oral route [2], and the recommended minimal clinically important difference of cumulative opioid consumption for postoperative analgesia is an absolute reduction of 10 mg intravenous morphine in 24 h [3], the study does not mention whether reported 24 h cumulative morphine consumption was oral or intravenous.…”
mentioning
confidence: 99%
“…We thank Drs Cafferkey and Ward [1] for their interest in our article [2]. To address the comment on the stylet's shape, we acknowledge its significance, as it substantially impacts the success of tracheal intubation.…”
mentioning
confidence: 99%